Clinical and demographic characteristics of people who smoke versus inject crystalline methamphetamine in Australia: Findings from a pharmacotherapy trial. (6th October 2020) - McKETIN, Rebecca; Quinn, Brendan; Higgs, Peter; Berk, Michael; Dean, Olivia M.; Turner, Alyna; Kelly, Peter J.; Lubman, Dan I.; Carter, Gregory; Baker, Amanda L.; Manning, Victoria; Thomas, Tamsin; et al.
Abstract: Introduction and Aims: There has been a rapid increase in smoking crystalline methamphetamine in Australia. We compare the clinical and demographic characteristics of those who smoke versus inject the drug in a cohort of people who use methamphetamine. Design and Methods: Participants ( N  = 151) were dependent on methamphetamine, aged 18–60 years, enrolled in a pharmacotherapy trial for methamphetamine dependence, and reported either injecting ( n  = 54) or smoking ( n  = 97) methamphetamine. Measures included the Timeline Followback, Severity of Dependence Scale, Amphetamine Withdrawal Questionnaire, Craving Experience Questionnaire and the Brief Psychiatric Rating Scale (symptoms of depression, hostility, psychosis and suicidality). Simultaneous regression was used to identify independent demographic correlates of smoking methamphetamine and to compare the clinical characteristics of participants who smoked versus injected. Results: Compared to participants who injected methamphetamine, those who smoked methamphetamine were younger and less likely to be unemployed, have a prison history or live alone. Participants who smoked methamphetamine used methamphetamine on more days in the past 4 weeks than participants who injected methamphetamine (26 vs. 19 days, P  = 0.001); they did not differ significantly in their severity of methamphetamine dependence, withdrawal, craving or psychiatric symptoms ( P  > 0.05). After adjustment for demographic differences, participants who smoked had lower craving [b (SE) = −1.1 (0.5), P  = 0.021] and were less likely to report psychotic symptoms [b (SE) = −1.8 (0.7), P  = 0.013] or antidepressant use [b (SE) = −1.1 (0.5), P  = 0.022]. Discussion and Conclusions: Smoking crystalline methamphetamine is associated with a younger less marginalised demographic profile than injecting methamphetamine, but a similarly severe clinical profile.